História em catálogos: um estudo da política editorial Zahar de 2001 a 2014 - Paul, Danielle Rosa (2015)
The following work addresses the editorial policies of Jorge Zahar, specifically from 2001 to 2014, discussing the challenges faced by this publishing house that has built the brand through the ideal of publishing books that remain on the market over time. The study presents its history, since the foundation as 'Zahar Editores', in the 1950s, describing the editorial proposals on the context of specific social and marketing situations. Some critical moments were highlighted, when both the editorial policies and the company's management structure were reassessed, resized, establishing a period of major changes. That said, this work aims to analyze different Zahar’s catalogs: one of the 1985 period - when the publisher house started to be managed by Jorge Zahar and his children - and the ones from 2001 to 2014, noticing the aspects of changes and similarities between all the catalogs and the editorial fund. The categories 'independent' and 'classical books' have been identified as strategic elements in the self-conception and external identification of the publishing house, pointing its perception of books as cultural assets, as well as the role of the editor as a cultural agent. The performance of Zahar has been challenging two types of diagnostics in the common sense and even in the academic literature. The first is that publishers need to invest in books that quickly reach high sales levels, even if they don’t last too long, in order to ensure profitability and presence in the market. The second is that, in general, small and medium publishing houses, still autonomous, tend to sell their copyrights to the largest and most capitalized companies, once they have to face the aggressive marketing policies of these organizations. The research findings suggest that Zahar has insisted on maintaining their self-identification as a publishing house of classical books, directing their editorial policies to the publication of materials that last longer, demonstrating that it is possible to follow their own path in terms of emphasizing the unique role the editor, marked by independence in choosing what, how, when and how many publications - and retaining its place in the market.